Apakah kejelasan sasaran anggaran dan sistem pelaporan memengaruhi akuntabilitas pengelolaan dana desa? - Ahaya, Ratin; Niswatin Niswatin; Usman Usman (Akuntansi dan Teknologi Informasi, 2024)
This research aims to determine the effect of clarity of budget targets and reporting system on accountability in village fund management in village throughout Asparaga Sub-District, Gorontalo Regency. The decrease in the amount of village funds received raise concern about the village's readiness in managing these funds. This research use quantitative methods using primary data obtained from questionnaire and measured using a likert scale. The data collection technique used a research questionnaire which was distributed to village officials with a total of 60 samples in this study. The tool used in this research is SPSS 27th version (statistical program for social science). Based on the results of the t test and f test of this research, it is known that clarity of budget targets and the reporting system has an influence on the accountability of village fund management. The clearer the budget targets and reporting systems in government, will help increase accountability in village fund management.